(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Capital structure represents the proportion of debt capital and equity capital in the capital structure. What kind of capital structure is best for a firm is very difficult to define. The capital structure should be such which increases the value of equity share or maximizes the wealth of equity shareholders.Debt and equity differ in cost and risk. As debt involves less cost but it is very risky securities whereas equity is expensive securities but these are safe securities from companies’ point of view.Debt is risky because payment of regular interest on debt is a legal obligation of the business. In case they fail to pay debt security holders can claim over the assets of the company and if firm fails to meet return of principal amount it can even go to liquidation and stage of insolvency.Equity securities are safe securities from company’s point of view as company has no legal obligation to pay dividend to equity shareholders if it is running in loss but these are expensive securities. The current paper highlights the parameters of capital structure.